Design of a High Power, LCC-Compensated, Dynamic, Wireless Electric Vehicle Charging System with Improved Misalignment Tolerance - ElGhanam, Eiman Ayman Mahmoud (2021)
Dynamic wireless power transfer (DWPT) systems are becoming increasingly important for on-the-move electric vehicle (EV) charging solutions, to overcome range anxiety and compensate for the consumed energy while the EV is in motion. In this work, a DWPT EV charging system is proposed to be implemented on a straight road stretch such that it provides the moving EV with energy at a rate of 308 Wh/km. This rate is expected to compensate for the vehicle’s average energy consumption and allow for additional energy storage in the EV battery. The proposed charging system operates at an average power transfer efficiency that is higher than 90% and provides good lateral misalignment tolerance up to ±200 mm. Details of the proposed system’s design are presented in this paper, including EV specifications, inductive link and compensation network design and power electronic circuitry.